Public Transport In Kashkadarya Region During The Years Of Independence - Rakhmonov Sukhayl Latipovich (Genius Journals, 2025)
This article analyzes the socio-economic changes that have occurred in the public transport sector in the Kashkadarya region since the Republic of Uzbekistan gained independence, the development of infrastructure, the introduction of modern vehicles, and the quality of transport services provided to the population.
Keywords: public transport; Kashkadarya; infrastructure